Effective coverage of antenatal care and associated factors among pregnant women in Tanzania: a multilevel analysis - Gebrekidan, Amanuel Yosef; Woldegeorgis, Beshada Zerfu; Kassie, Gizachew Ambaw; Haile, Kirubel Eshetu; Abrha, Ashenafi Teklay; Asnake, Angwach Abrham; Asgedom, Yordanos Sisay (Frontiers in Global Women's Health, 2025)
BackgroundAntenatal care (ANC) is a crucial part of reproductive health care, providing opportunities for health promotion, screening, diagnosis, and illness prevention. However, evidence has shown that poor-quality ANC is prevalent. Therefore, this study aimed to investigate the effective coverage (quality-adjusted coverage) of ANC and its associated factors among pregnant women in Tanzania.MethodsThis research was based on data from the 2022 Tanzania Demographic and Health Survey. The study utilized a weighted sample of 3,890 pregnant women. Given the influence of clustering and the binary nature of the outcome variable, we used a multilevel binary logistic regression model. Statistical significance was determined using the adjusted odds ratio (AOR) with a 95% confidence interval (CI), taking into account the model with the lowest deviation that best matched the data.ResultsIn this study, the effective coverage of ANC was 39.3% [95% confidence interval (CI): 37.8, 40.8]. After considering both individual- and community-level variables, women's age, educational status, husbands’/partners’ employment status, wealth index, number of ANC visits, administrative zones, and urban residence were all found to have statistically significant associations with effective ANC coverage among pregnant women in Tanzania.ConclusionOnly four out of ten pregnant women received effective ANC (quality-adjusted ANC), underscoring that crude coverage and access to healthcare do not ensure quality ANC. Emphasis should be placed on integrating component-based indicators. Furthermore, all attempts to provide all components should be considered during women's first visit, in addition to the need to increase the number of visits by pregnant women. Additionally, more attention should be paid to disadvantaged groups in terms of wealth and residence, and the fee exemption strategy should be supported by boosting the availability of healthcare supplies, particularly in remote areas.